The neurosteroid allopregnanolone sulfate inhibits Nav1.3 α subunit-containing voltage-gated sodium channels, expressed in Xenopus oocytes - Takafumi Horishita; Nobuyuki Yanagihara; Susumu Ueno; Dan Okura; Reiko Horishita; Tomoko Minami; Yuichi Ogata; Yuka Sudo; Yasuhito Uezono; Takashi Kawasaki (Elsevier, 2018)
The neurosteroid allopregnanolone has potent analgesic effects, and its potential use for neuropathic pain is supported by recent reports. However, the analgesic mechanisms are obscure. The voltage-gated sodium channels (Nav) α subunit Nav1.3 is thought to play an essential role in neuropathic pain. Here, we report the effects of allopregnanolone sulfate (APAS) on sodium currents (INa) in Xenopus oocytes expressing Nav1.3 with β1 or β3 subunits. APAS suppressed INa of Nav1.3 with β1 and β3 in a concentration-dependent manner (IC50 values; 75 and 26 μmol/L). These results suggest the possible importance of Nav1.3 inhibition for the analgesic mechanisms of allopregnanolone. Keywords: Allopregnanolone sulfate, Voltage-gated sodium channel α subunit Nav1.3, Neuropathic pain